Efeitos da adição de Al2O3 na liga stellite 6 para a realização de revestimento superficial pelo processo GTAW-P - Moreira, Eduardo Ferracin (2019)
This work aimed to investigate the effect that the addition of aluminum oxide brought to the surface coatings made with the alloy, cobalt-based, Stellite 6 and deposited by the GTAW-P welding process. For this, three mixtures of Al2O3 + Stellite 6 with variations of aluminum oxide concentration were made, in which such mixtures were used to coat SAE 1020 carbon steel. After the deposition, a greenish "shell" was observed on the surface of the coatings due to the formation of oxides and after preparation of the test specimens, it was found that there was a large dilution of the powder deposited on the substrate. The coatings reached values of microhardness in the range of 400 Hv to 500 Hv, such numbers corresponded to the values found in the literature for pure Stellite 6 alloy. The micrographs converged with the results of other researchers, in which a more refined microstructure was noticed in the surface region of the coating. The diffractograms presented the formation of the characteristic phases of Stellite 6, being the carbides type M7C3 and M23C6, elements of CoCr and Co isolated. In addition to these phases, the presence of phases formed through the addition of aluminum oxide, Al2O3, CAl4O4 and Cr2O3, was confirmed. Thus, the incorporation of alumina maintained the main characteristics of the coatings of Stellite 6, allowed the formation of oxides. To determine the influence of aluminum oxide on the wear of the coats, it is necessary to perform wear tests of the Pin-disc type and Rubber Wheel, such tests will remain for future work. However, the results indicate that with proper control of the process dilution, coating properties, such as microhardness and abrasive wear resistance, improve.